Discrete modeling of fin-and-tube heat exchangers with cross-fin conduction functionality. (August 2019) - Sarfraz, Omer; Bach, Christian K.; Bradshaw, Craig R.
Highlights: Coil model with no cross fin-conduction has increased bias to underpredict capacity. The addition of cross fin conduction to the model reduces the amount of bias. Cross-fin conduction is important in coil when its system(s) is inactive. It increases with increased difference in air and water temperatures at coil inlet. Abstract: Modeling of heat exchanger coils is an important step of developing predictive simulation platforms which allow for a model-based design of new equipment. These simulation models, if accurate enough, the experimental iterations needed during new product development, will reduce overall development cycle time and cost. Fin-and-tube heat exchanger coils are used extensively in residential and commercial heating, ventilation, and air-conditioning (HVAC) systems. Many of the current state-of-the-art heat exchanger models do not account for cross-fin conduction between tubes and struggle with a predictive accuracy of the coils under a non-uniform air flow and especially with a large temperature difference between the adjacent tubes. This paper presents a detailed segment-by-segment model of a fin-tube heat exchanger that calculates the conduction between all the adjacent tube segments through the fins (e.g. "cross-fin conduction"). The physics of the model includes both refrigerant and air side phase change transitions as well as the ability to account for air and refrigerant flow maldistribution. The model's predictions are compared against experimental results collected from an industrial heat exchanger test facility for an air-to-water heat exchanger. A preliminary set of results confirm that cross-fin conduction between heat exchanger tube segments accounts for significant discrepancies in predicted coil performance, particularly with a large temperature difference between the adjacent tubes.